School Transportation Planning Using PTV Visum 2025 - Halawa, Desni Barani Sondrara; Reza Yoga Anindita (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2025)
The problem of school transportation is a serious concern. This can be seen from the low interest of students in using public transportation due to suboptimal service and poor fleet conditions. This study aims to plan school transportation for students. The stages of this study consist of data collection, school transportation analysis and interpretation of results. The results of the analysis show the potential demand for school transportation of 13,416 students, resulting in 7 routes serving 36 schools. These routes are between 4.75 km and 23.6 km long and use the Isuzu NQR 71 fleet with a capacity of 33 passengers, operating 6 days a week with 3 shifts: morning (06.00–07.30), afternoon (11.45–15.00) and evening (15.01–17.30), speed 35 km/hour and target load factor 100%. Travel time ranges from 5-60 minutes, vehicle circulation time 13-105 minutes, number of rit 1-4 rit, with headway between 1-4 minutes depending on shift, and number of fleet 1-76 fleets (Isuzu NQR 71). The results of this analysis are expected to provide a significant contribution to the Samarinda City Transportation Agency in planning school transportation.